Informality, Public Employment and Employment Protection in Developing Countries - Shaimaa Yassin; François Langot (Institute of Labor Economics (IZA), 2017)
This paper proposes an equilibrium matching model for developing countries' labor markets where the interaction between public, formal private and informal private sectors are taken into account. Theoretical analysis shows that gains from reforms aiming at liberalizing formal labor markets can be annulled by shifts in the public sector employment and wage policies. Since the public sector accounts for a substantial share of employment in developing countries, this approach is crucial to understand the main labor market outcomes of such economies. Wages offered by the public sector increase the outside option value of the workers during the bargaining processes in the formal and informal sectors. It becomes more profitable for workers to search on-the-job, in order to move to these more attractive and more stable types of jobs. The public sector therefore acts as an additional tax for the formal private firms. Using data on workers' flows from Egypt, we show empirically and theoretically that the liberalization of labor markets plays against informal employment by increasing the profitability, and hence job creations, of formal jobs. The latter effect is however dampened or even sometimes nullified by the increase of the offered wages in the public sector observed at the same time.
Keywords: E24; E26; J60; J64; O17; 330; job search; informality; public sector; Egypt; unemployment; wages; policy interventions